Mortality and cardiovascular diseases risk in patients with Barrett's oesophagus: a population‐based nationwide cohort study. Issue 7 (31st January 2017) - Erichsen, R.; Horvath‐Puho, E.; Lund, J. L.; Dellon, E. S.; Shaheen, N. J.; Pedersen, L.; Davey Smith, G.; Sørensen, H. T.
Summary: Background: Patients with Barrett's oesophagus may be at increased risk of mortality overall, and cardiovascular disease has been suggested as the main underlying cause of death. Aim: To examine cause‐specific mortality and risk of cardiovascular events among patients with Barrett's oesophagus. Methods: Utilising existing Danish data sources (1997–2011), we identified all patients with histologically verified Barrett's oesophagus ( n = 13 435) and 123 526 members of the general population matched by age, sex and individual comorbidities. We calculated cause‐specific mortality rates and incidence rates of cardiovascular diseases. We then compared rates between patients with Barrett's oesophagus and the general population comparison cohort, using stratified Cox proportional hazard regression. Results: Patients with Barrett's oesophagus had a 71% increased risk of overall mortality. The cause‐specific mortality rate per 1000 person‐years for patients with Barrett's oesophagus was 8.5 for cardiovascular diseases, 14.7 for non‐oesophageal cancers, and 5.4 for oesophageal cancer. Compared to the general population cohort, corresponding hazard ratios were 1.26 (95% confidence interval (CI): 1.15–1.38), 1.77 (95% CI: 1.65–1.90), and 19.4 (95% CI: 16.1–23.4), respectively. The incidence rates of cardiovascular diseases per 1000 person‐years for Barrett's oesophagus patients and for persons from the general population cohort, respectively, varied from 0.4 and 0.2 for subarachnoid bleeding (hazard ratio 1.10, 95% CI: 0.87–1.39) to 8.1 and 5.9 for congestive heart failure (hazard ratio 1.33, 95% CI: 1.21–1.46). Conclusion: Prophylactic measures targeted at cardiovascular diseases and non‐oesophageal cancers potentially could be more important than measures against oesophageal cancer, for improving prognosis among patients with Barrett's oesophagus. Abstract : Linked Content This article is linked to Kilincalp and Altiner and Richter papers. To view this article visithttps://doi.org/10.1111/apt.14904 andhttps://doi.org/10.1111/apt.14001 .